2022
DOI: 10.3389/fpls.2022.1005991
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of microalgae and their application to sustainable agriculture: A mini-review

Abstract: Concern that depletion of fertilizer feedstocks, which are a finite mineral resource, threatens agricultural sustainability has driven the exploration of sustainable methods of soil fertilization. Given that microalgae, which are unicellular photosynthetic organisms, can take up nutrients efficiently from water systems, their application in a biological wastewater purification system followed by the use of their biomass as a fertilizer alternative has attracted attention. Such applications of microalgae would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 97 publications
0
7
0
1
Order By: Relevance
“…A similar research result has also been reported by Kim et al [ 26 ], who demonstrated significant increases in shoot height, leaf thickness, and leaf pigments of the strawberry cultivar ‘Seolhyang’ by C. fusca CHK0059 application. Moreover, the promoting effect on plant growth performance by microalgae application has been reported in various crops, such as wheat, rice, maize, lettuce, tomato, cabbage, etc., as reviewed in Lee and Ryu [ 23 ] and Çakirsoy et al [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar research result has also been reported by Kim et al [ 26 ], who demonstrated significant increases in shoot height, leaf thickness, and leaf pigments of the strawberry cultivar ‘Seolhyang’ by C. fusca CHK0059 application. Moreover, the promoting effect on plant growth performance by microalgae application has been reported in various crops, such as wheat, rice, maize, lettuce, tomato, cabbage, etc., as reviewed in Lee and Ryu [ 23 ] and Çakirsoy et al [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, microalgae consistently showed a nutrient removal efficiency against nitrates, phosphates, organic carbon, ammonia and other nutrients above 70%, and in a few cases above 90% from the initial levels ( Abdelfattah et al., 2022 ; Nagarajan et al., 2022 ). The ability of microalgae to absorb nutrients in abundance could be attributed to the special physiological mechanisms such as carbon concentration mechanism, lipid remodeling and P allocation in fast-growing microalgae as described earlier ( Çakirsoy et al., 2022 ). Microalgae prefer ammonia over inorganic N sources as their assimilation is less energy intensive and can be directly incorporated into AAs and other N moieties ( Sarma et al., 2021 ).…”
Section: Production Of Microalgae Based Bio Fertilizers and Biostimul...mentioning
confidence: 96%
“…This luxury uptake mechanism is further supported by additional physiological processes such as membrane lipid remodeling to reallocate P based on its availability from surrounding medium. This is achieved through modulation of lipid composition, where P starvation induces remodeling of membrane lipid moieties such as phosphatidylethanolamine, phosphatidylcholine, and phosphatidylglycerol (phospholipids) to non-P containing glycolipids or betaine class of lipids such as sulfoquinovosyldiacylglycerol or diacylglyceroltrimethylhomoserine leading to P reallocation ( Çakirsoy et al., 2022 ). Such physiological mechanisms offer microalgae to accommodate additional P from surrounding medium or reallocate P during P deficiency by way of polar lipid remodeling as observed in few fast growing and high P uptake microalgae species such as Nanochloropsis oceania, Nannochloropsis gaditana, Tetraselmis suecia ( Cañavate et al., 2017 ).This phenomenon of luxury uptake of P by microalgae could be utilized for delivering soluble P to plants.…”
Section: Growth-promoting Properties Of Microalgaementioning
confidence: 99%
See 1 more Smart Citation
“…게 다가 최근에는 클로렐라를 생물비료로 개발하여 국내외 농업 분야에 활용하고 있다 [8,9]. 클로렐라 시비에 의한 작물생산성 및 품질 향상에 관련된 연구결과는 밀(Triticum aestivum), 토마토(Solanum lycopersicum), 배추(Brassica oleracea), 무(Raphanus raphanistrum), 시금치(Spinacia oleracea), 상 추(Lactuca sativa), 양파(Allium cepa) 등 다양한 작물을 대 상으로 보고되었다 [10][11][12][13][14]. 현재 국내의 많은 딸기(Fragaria x ananassa) 재배 농가 에서도 이러한 클로렐라 시비 농법이 적용되고 있으며, 딸기의 생육증진 및 병충해 방제뿐만 아니라 과실의 당도 및 수확량 향상 등 긍정적 효과로 인해 딸기농가의 수익성이 증가하고 있 다 [4,11,15] 딸기유묘의 엽록소 및 카로테노이드 함량 또한 고형 클로 렐라 시비에 의해 증가되었다(Fig.…”
unclassified